2020
DOI: 10.1371/journal.pone.0238440
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric dimethylarginine in dogs with myxomatous mitral valve disease at various stages of disease severity

Abstract: Symmetric dimethylarginine (SDMA) is a serum biomarker of renal damage in dogs. Moreover, SDMA concentration is an independent predictor of development of severe heart failure (HF) in humans with cardiac disease. This study evaluates whether the serum concentration of SDMA in dogs with myxomatous mitral valve disease (MMVD) is influenced by the severity of heart disease, pulmonary hypertension (PH) and treatment of HF. A total of 99 client-owned dogs were included in this retrospective case-control study; 78 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…This finding confirms the results of a previous prospective study in which SDMA was correlated with cardiac disease severity and with echocardiographic parameters of left atrio-ventricular dilation ( 14 ). Conversely, two other retrospective studies failed to demonstrate a correlation between SDMA and MMVD progression ( 36 , 37 ). The discrepancy between our study and these latter studies can be explained by differences in study design and laboratory analytical method used to determine SDMA.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This finding confirms the results of a previous prospective study in which SDMA was correlated with cardiac disease severity and with echocardiographic parameters of left atrio-ventricular dilation ( 14 ). Conversely, two other retrospective studies failed to demonstrate a correlation between SDMA and MMVD progression ( 36 , 37 ). The discrepancy between our study and these latter studies can be explained by differences in study design and laboratory analytical method used to determine SDMA.…”
Section: Discussionmentioning
confidence: 88%
“…In the study of Savarese et al no therapies effect has been shown ( 36 ), whereas in the other study increasing doses of furosemide seemed to be associated with an increase of SDMA concentrations. However, the combined analysis of therapy effect with MMVD ACVIM stage did not show any significant result ( 37 ). Cardiovascular therapy effect on SDMA in dogs with MMVD is still unclear and, so far, it is not possible to discriminate if the variation of SDMA concentrations is more influenced by cardiovascular drugs effect on glomerular filtration rate, or by the cardiac disease itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary arterial pressure was estimated solely by measuring the TR velocity. Pulmonary hypertension was assessed using three different cut-offs: ≥2.8 m/s [ 26 , 27 ], >3 m/s [ 10 , 28 ], and >3.4 m/s [ 29 ].…”
Section: Methodsmentioning
confidence: 99%